Maternal Psychological Distress and Separation Anxiety Disorder in Children - Mofrad, Sakineh; Abdullah, Rohani; Abu Samah, Bahaman; Mansor, Mariani; Baba, Maznah (Eurojournals, 2009)
The psychological wellbeing of parents have consistently been found to be a major risk factor for child development. However, few studies have been conducted on parental psychological wellbeing in relation to separation anxiety disorder (SAD) in particular. The current study examined the relationship between psychological distress in mothers and SAD symptoms in children. A total of 120 children in first grade school and their mothers participated in the study. SAD was measured using SAAS_C while maternal psychological distress was assessed using GHQ_28. There was evidence that significant and positive relationship existed between maternal anxiety and SAD in children. Maternal anxiety was the main predictor for SAD in this study. The result highlights the psychological constructs which may be relevant for the assessment and intervention in children suffering from SAD.